(2.5-3x) : 1 2/3 = (8/5+2x) : -8/17

(2.5-3x) : 1 2/3 = (8/5+2x) : -8/17

Share

1 Answer

  1. Đáp án:

    Giải thích các bước giải:

    \[\begin{array}{l}\left( {2.5 – 3x} \right):1{\rm{ }}2/3{\rm{ }} = {\rm{ }}\left( {8/5 + 2x} \right){\rm{ }}:{\rm{ }} – 8/17\\ \Leftrightarrow \left( {2,5 – 3x} \right):1\frac{2}{3} = \left( {\frac{8}{5} + 2x} \right):\frac{{ – 8}}{{17}}\\ \Leftrightarrow \left( {\frac{5}{2} – 3x} \right).\frac{3}{5} = \left( {\frac{8}{5} + 2x} \right).\frac{{ – 17}}{8}\\ \Leftrightarrow \frac{3}{2} – \frac{9}{5}x = \frac{{ – 17}}{5} – \frac{{17}}{4}x\\ \Leftrightarrow – \frac{9}{5}x + \frac{{17}}{4}x = \frac{{ – 17}}{5} – \frac{3}{2}\\ \Leftrightarrow \frac{{49}}{{20}}x = \frac{{ – 49}}{{10}}\\ \Leftrightarrow x = \frac{{ – 49}}{{10}}.\frac{{20}}{{49}}\\ \Leftrightarrow x = – 2\end{array}\]

    • -1
Leave an answer

Leave an answer

Browse